PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, LEVERAGE, PROFITABILITAS DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP LUAS PENGUNGKAPAN SUKARELA - Rina Mukti, 09.05.52.0069; Indarti, M.G. Kentris (Students Journal of Accounting and Banking, 2013)
This study was conducted to examine some of the factors that influence the voluntary disclosure in corporate annual reports factors that constitute the independent variables are firm size, liquidity, leverage, profitability and public ownership. Methods of sample selection is purposive sample samplingdengan manufacturing companies in Indonesia. The data of this study was the period 2011-2012 annual report of 138 manufacturing companies in Indonesia Stock Exchange. Results of this study showed that of the t test is known variables firm size and leverage variables significant positive effect on widespread voluntary disclosure. variable liquidity, profitabi; itas and public ownership does not significantly influence the wider voluntary disclosure because the value of t is greater tha 0.05.Keywords: Voluntary Disclosure, company size, liquidity, leverage, profitability,Â Â  and the Public Shareholders.